Analyzing the filler and activity effect of fly ash and slag on the early hydration of blended cement based on calorimetric test. (22nd March 2021) - Wu, Meng; Sui, Shiyu; Zhang, Yunsheng; Jia, Yantao; She, Wei; Liu, Zhiyong; Yang, Yonggan
Abstract: To increase the utilization rate of supplementary cementitious materials (SCMs), the filler effect and activity effect of low-calcium fly ash (LFA) and ground granulated blast furnace slag (GGBFS) on the early hydration of blended cement were analyzed based on calorimetric test. The test results showed that the full-width at half-maximum (FWHM) value of exothermic peak from calorimetric test could be used to analyze and compare the filler effect of different mineral admixtures in blended cement. The filler effect of GGBFS had less influence on the early hydration of blended cement compared to LFA, and the activity effect of GGBFS in blended cement played a crucial role gradually after 48 h of hydration. Compared to GGBFS, the filler effect of LFA played a significant role at accelerating and decelerating period of blended cement hydration. However, the activity effect of LFA was restrained at 3d. Even the activity effect of LFA was negligible in the first 7 days of hydration when blended cement contained high volume LFA.